A survey of the preservation programs/practices adopted for historical collections and archival materials in selected research and academic libraries and archives in Metro Manila - Datiles, Clarita P. (1987)
This research study investigates the status of preservation programs/practices adopted for historical collections and archival materials in major academic and research libraries and archives in Metro Manila. It also seeks to identify the types of historical collections and archival materials available in the 13 respondent institutions that participated in this survey. The libraries surveyed include the American Historical Collection (AHC); The Eugenio Lopez Foundation, Inc./Lopez Memorial Museum (ELFI/LMM); The National Library (TNL); the University of the Philippines' Jorge B. Vargas Filipiniana Research Center (UPJBVFRC); the De La Salle University Library's Filipiniana Section (DLSUL/FS); and the Ateneo de Manila University's Rizal Library Special Collections (ADMURL/SC). The archives group, on the other hand, include the Archives of the Archdiocese of Manila (AAM); the Ayala Museum Library and Iconographic Archives (AMLIA); the Philippine Province Archives of the Society of Jesus (PPASJ); the Records Management and Archives Office (RMAO); the University of the Philippines Library/University Archives and Records Center (UP/UARC); the Ateneo de Manila University Archives (ADMUA); and the University of Santo Tomas Archives (USTA). All these institutions, except for the University of the Philippines' Jorge B. Vargas Filipiniana Research Center (UPJBVFRC), have systematic preservation programs operating in their respective libraries and archives.